2011
DOI: 10.3390/ijms12106952
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Anti-Listerial Activities of Crude n-Hexane and Aqueous Extracts of Garcinia kola (heckel) Seeds

Abstract: We assessed the anti-Listerial activities of crude n-hexane and aqueous extracts of Garcinia kola seeds against a panel of 42 Listeria isolates previously isolated from wastewater effluents in the Eastern Cape Province of South Africa and belonging to Listeria monocytogenes, Listeria grayi and Listeria ivanovii species. The n-hexane fraction was active against 45% of the test bacteria with zones of inhibition ranging between 8–17 mm, while the aqueous fraction was active against 29% with zones of inhibition ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…16,[25][26] Therefore, the variation in MICs seen with different studies and also different antibacterial activities reported from extracted fractions could be due to methods and solvent used in the various extractions procedure. Other workers like Penduka and Okoh 22 reported MIC of 10mg/ml. Therefore, it is important to harmonise the extraction procedure so as to see a consistent and reproducible results that will serve as a reference.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…16,[25][26] Therefore, the variation in MICs seen with different studies and also different antibacterial activities reported from extracted fractions could be due to methods and solvent used in the various extractions procedure. Other workers like Penduka and Okoh 22 reported MIC of 10mg/ml. Therefore, it is important to harmonise the extraction procedure so as to see a consistent and reproducible results that will serve as a reference.…”
Section: Discussionmentioning
confidence: 90%
“…It was also found to be active against a strain of Candida albicans clinical isolate (CFI 1), an observation that was similar to the work of Penduka and Okoh. 22 The butanol fraction of the extract was found to be active against all the A. baumannii isolates and candida albicans (CFI 1). According to Akinpelu et al 16 butanol extract of G. kola, exhibited antibacterial activity against Bacillus anthracis and E. coli sensitive isolates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The extracts were prepared using the method of Basri and Fan [ 20 ] as outlined by Penduka and Okoh [ 21 ]. Briefly, the method involved the steeping of the seed powder in n-hexane solvent for 48 h with shaking in an orbital shaker at 50 rpm (Stuart Scientific Orbital Shaker, UK), followed by centrifugation at 3 000 rpm for 5 min (Beckman Model TJ-6RS Centrifuge, UK), filtration using a Whatman no.…”
Section: Methodsmentioning
confidence: 99%